The Application of Draping Techniques in Zero-Waste Fashion Design Using Pekalongan Batik Fabric - Mursidah Mursidah; Andri Nur Cahyo (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
Abstract. Batik is the result of creating motifs which consists of the integrity of the arrangement of ornaments that decorate the surface of the fabric. Batik motifs are noble works of art because they are philosophical, the basic idea behind the birth of the patterns is the creator's philosophy of life and cosmology. In ancient times, batik fabric was not allowed to have cut motifs and was only wrapped around the human body. But now, batik has developed following fashion trends. For fashion production, batik fabric is processed through cutting with contemporary patterns or models. This will unknowingly reduce the essence of creating batik motifs and their use. In the development of fast fashion, the fashion industry has contributed a lot of waste that damages the environment. One way to reduce this is with zero waste fashion. This article contains a discussion about how to apply the zero waste fashion concept to Pekalongan batik cloth. The zero waste concept used is by applying draping techniques to construct fabric without cutting the material into one complete fashion model. Applying the draping technique to Pekalongan batik cloth makes batik fashion without cutting the material so it doesn't produce waste. Apart from that, batik motifs can appear in their entirety without being cut, just like the initial essence of batik cloth created. The zero waste fashion concept provides greater opportunities for the Pekalongan batik industry so that it does not have a negative impact on the environment and is more sustainable.